AID recruits the RNA exosome to degrade HIV‐1 nascent transcripts through interaction with the Tat‐P‐TEFb‐TAR RNP complex. Issue 2 (5th January 2018) - Wang, Ruixuan; Zhang, Xiaowei; Ding, Haibo; Qiao, Ying; Han, Xiaoxu; Geng, Wenqing; Guan, Gefei; Cui, Hualu; Zhao, Bin; Wu, Yuntao; Liang, Guoxin; Shang, Hong
Abstract : Activation‐induced cytidine deaminase (AID), a member of the APOBEC family that induces antibody diversification, has been shown to inhibit the replication of hepatitis B virus, Kaposi's sarcoma‐associated herpesvirus, and retro‐transposons. However, whether AID can inhibit human immunodeficiency virus 1 (HIV‐1) replication remains unclear. Here, we report that AID impairs the synthesis of HIV‐1 components by interacting with the complex of Tat. This interaction recruits the RNA exosome to degrade the nascent HIV‐1 transcript. AID also targets the HIV‐1‐integrated genome via the Tat‐P‐TEFb‐TAR complex. Thus, we propose a novel function for AID as an adaptor protein that represses viral transcription. Our findings provide insights into developing anti‐HIV therapeutics and understanding how host cells restrict integrated virus replication. Abstract :